2017
DOI: 10.1016/j.celrep.2017.02.030
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K4 Controls the Chromatin Modifier HDAC6 during Trophoblast Stem Cell Epithelial-to-Mesenchymal Transition

Abstract: SUMMARY The first epithelial to mesenchymal transition (EMT) occurs in trophoblast stem (TS) cells during implantation. Inactivation of the serine/threonine kinase MAP3K4 in TS cells (TSKI4 cells) induces an intermediate state of EMT, where cells retain stemness, lose epithelial markers, and gain mesenchymal characteristics. Investigation of relationships between MAP3K4 activity, stemness, and EMT in TS cells may reveal key regulators of EMT. Here, we show that MAP3K4 activity controls EMT through the ubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 25 publications
3
52
1
Order By: Relevance
“…In the outgrowth assay, abnormal TGC development was evaluated with a TGC marker (Tfap2c), the total areas of outgrowth, and the ICM/TE ratio. Taken together, our findings support the importance of TJs and critical functional roles for trophoblast and further development (DaSilva‐Arnold, Zamudio, Al‐Khan, & Illsley, ; Mobley et al, ; Sivasubramaniyam et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the outgrowth assay, abnormal TGC development was evaluated with a TGC marker (Tfap2c), the total areas of outgrowth, and the ICM/TE ratio. Taken together, our findings support the importance of TJs and critical functional roles for trophoblast and further development (DaSilva‐Arnold, Zamudio, Al‐Khan, & Illsley, ; Mobley et al, ; Sivasubramaniyam et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, recent studies have demonstrated the TJ regulatory mechanism during the epithelial to mesenchymal transition and the importance of trophectoderm differentiation via TJs (Calder, Edwards, Betts, & Watson, 2017;Davies et al, 2016;Mobley et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our findings support the importance of tight junction and critical functional roles for trophoblast development and further development (Sivasubramaniyam et al, 2013;DaSilva-Arnold et al, 2016;Mobley et al, 2017).…”
Section: Resultssupporting
confidence: 78%
“…We have previously demonstrated that MAP3K4 inhibits HDAC6 expression and activity ( Mobley et al, 2017 ). HDAC6 induces EMT in TS cells by binding to the promoters of epithelial maintenance genes, deacetylating histone H2BK5, and repressing gene expression.…”
Section: Resultsmentioning
confidence: 99%